A journey through history by the "old road to Segovia", Fuenfría valley in Cercedilla (Madrid, Spain) - Rodríguez Morales, Jesús; García-Rodríguez, Manuel (Observatorio Medioambiental, 2017)
This paper describes the three main ancient roads of the Valley of the Fuenfría in Cercedilla, Madrid, Spain: the official "Roman road", the "old road to Segovia" and the "Bourbon road". Below are described the criteria that make it more likely that the one built in Roman times is the "Old Path to Segovia", climatic, engineering, archaeological, geological and geomorphological.
Keywords: Roman Road; Valley of the Fuenfría; tafoni; Sierra de Guadarrama National Park.